Diagnostic and interactive uses of budgets and the moderating effect of strategic uncertainty / Sabrina Shi Qiong Shen and Sujatha Perera - Shi, Sabrina Qiong Shen; Perera, Sujatha (Accounting Research Institute (ARI), 2012)
The existing literature suggests that under certain environmental conditions control systems such as budgets can be effective only if they are used interactively. However, empirical evidence to support such a proposition is scant. This study examines the moderating effect of strategic uncertainty on the effectiveness of budgets when used as (a) a diagnostic control system; and (b) an interactive control system. In examining these relationships, the intervening role of individual motivation is also considered. Findings based on the data gathered from a questionnaire survey of large and medium size public sector organisations in Australia confirm that while diagnostic use of budgets is more effective in motivating individual performance under low strategic uncertainty, interactive use of budgets is more effective when strategic uncertainty is high. This study contributes to both the theory and practice.